1989
DOI: 10.1104/pp.90.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Singlet Oxygen Quenchers and pH on the Bacterially Induced Hypersensitive Reaction in Tobacco Suspension Cell Cultures

Abstract: Suspension cell cultures of Nicotiana tabacum L. inoculated with the incompatible pathogen Pseudomonas syringae pv pisi undergo a hypersensitive reaction. Addition of the singlet oxygen quencher bixin to cell suspensions had no effect on hypersensitive cell death. Addition of the singlet oxygen quencher 1,4-diazabicyclo octane (DABCO) increased the medium pH and delayed the onset of cell death. This delay was eliminated when cell suspensions were buffered, and could also be induced by increasing medium pH with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Not surprisingly, a recent study into the effects of singlet oxygen scavengers on the hypersensitive reaction of tobacco cells towards P. syringae pv. pisi found that singlet oxygen was not generated during the host response [107]. ************************** While the hydroxyl radical has been proposed as the radical species most likely to be responsible for initial lesions created in the presence of superoxide-generating systems [55,62], there have been very few studies directed specifically at investigating this possibility in the case of plant-pathogen interactions.…”
Section: Bacterial Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, a recent study into the effects of singlet oxygen scavengers on the hypersensitive reaction of tobacco cells towards P. syringae pv. pisi found that singlet oxygen was not generated during the host response [107]. ************************** While the hydroxyl radical has been proposed as the radical species most likely to be responsible for initial lesions created in the presence of superoxide-generating systems [55,62], there have been very few studies directed specifically at investigating this possibility in the case of plant-pathogen interactions.…”
Section: Bacterial Pathogensmentioning
confidence: 99%
“…It is still being suggested [73,107] that singlet oxygen, generated from H0 2 /0 2~ via Equation (6) or by spontaneous dismutation, might play an important role in plant resistance. As discussed earlier in this review, singlet oxygen generation by these routes has been discounted [47,89,97,121].…”
Section: Bacterial Pathogensmentioning
confidence: 99%
“…2 Abbreviations: HR, hypersensitive reaction; HO, hydroxyl radical; MSA, methanesulfinic acid; MDA, malondialdehyde. the membrane symptoms of HR (23). Other active oxygen species, such as HO, have been implicated as the cause of cellular damage (5).…”
mentioning
confidence: 99%
“…This enzyme attacks unsaturated fatty acids in membranes, and produces both singlet oxygen and superoxide (02-). There are indications that singlet oxygen is not directly involved in hypersensitive reactions, but is converted to 02- (209). In some plants, rapid cell death may be caused by disruption of the tonoplast due to lipid peroxidation (64) which releases toxic phenolic compounds previously sequestered.…”
Section: Rydb Ex a W Hill)mentioning
confidence: 99%